STUDYING THE WORK OF ALISHER NAVOI DURING THE PERIOD OF INDEPENDENCE - Usmonova Sharifa Gulamovna (Bright Mind Publishing, 2025)
The study of Alisher Navoi’s work during the period of independence has gained significant momentum as his literary legacy has been reassessed in the context of national identity, cultural revival, and linguistic pride. With Uzbekistan’s independence, Navoi’s contributions to the Uzbek language, literature, and moral philosophy have been revisited through educational reforms, academic research, and cultural initiatives. His role in shaping linguistic nationalism, ethical governance, and spiritual discourse has been widely recognized. International scholarship, artistic expressions, and digital technologies have further expanded his influence. This paper explores the renewed appreciation of Navoi’s works, emphasizing their impact on national consciousness and intellectual growth in modern Uzbekistan.
Keywords: Alisher Navoi, Uzbekistan independence, Uzbek language, national identity, cultural revival, literary heritage, linguistic nationalism, ethics, governance, Sufism, digital humanities.